THE MODEL OF CONTROL VIA A WIRELESS COMMUNICATION CHANNEL BASED ON PROBABILISTIC ALGORITHMS OF CRYPTOGRAPHIC TRANSFORMATIONS - V. A. Kozlov; V. A. Ryndjuk; K. O. Bondarenko; V. O. Khachatryan (Современная наука и инновации, 2022)
Describes a probabilistic control model remote object via an open communication channel, comprising the procedures of authorization and authentication of governors of the coded signals to the control object via the wireless communication channel. The authentication procedure of the control signals is carried out by processing of the control codes by a probabilistic algorithm of cryptographic transformation, which allows to obtain for each communication session the new unique cipher codes control actions. The algorithm is implemented by introducing into his scheme initialization vector which is transmitted to the control object in encrypted form, together with the cipher of the control action. Given a description of several applications realized by the use of probabilistic algorithm for the cryptographic transformation.